Palliative care, shared care - Beatriz Lozano López; María Mercedes Huertas Pérez (Universidad de Alicante, 2018)
Objective: The main objective of this review is to present the relationship and the importance of nurses and family care in the last stage of life of terminally ill patients. Methods: Literature review Cuiden bases, PubMed, Medline, Cochrane and Scielo data. 57 records were obtained after combining the different keywords. It ended with the reading of the 28 selected documents. Results: The family plays a very important role in the decisions made about their care and the patient's wishes. For this it is necessary to work in teams; the multidisciplinary team with the family should work with the same goal, personalized and comprehensive patient care, pain and other symptoms and improve the quality of life of patients and their families. Conclusions: Palliative care from a comprehensive approach to terminal illness in its various dimensions, is considered the act of dying as a human act which are involved both health professionals and their families.